DARI BERPIKIR KE MEMBACA TEKS AI: DAMPAK PENGGUNAAN CHATGPT DAN GAMMA AI DALAM TUGAS MAKALAH DAN PRESENTASI TERHADAP NALAR KRITIS MAHASISWA - Rosalinda Samba’ Langi’; Tridio Patiku; Rein Patoding; Presdioyono; Mersiana Pongtasik (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This article examines the impact of ChatGPT and Gamma AI on students' academic processes, particularly in writing papers and presentations, and their implications for critical thinking. This research is motivated by students' increasing reliance on artificial intelligence technology, which provides instant information and assignment structure, potentially altering their learning patterns. Using a descriptive qualitative approach, this study involved observation, in-depth interviews, and document analysis to explore how AI technology affects students' knowledge construction processes, reading patterns, writing quality, and presentation skills. The results indicate that students tend to shift from analytical reading patterns to consumptive reading patterns due to the presence of instant summaries and automated materials. Other findings suggest a risk of reducing critical thinking skills when students rely more on AI output than on the analysis, evaluation, and synthesis processes that should be at the core of academic activities.